2006
DOI: 10.1159/000089798
|View full text |Cite
|
Sign up to set email alerts
|

Combined Multimodal Approach to the Treatment of Metastatic Anal Carcinoma: Report of a Case and Review of the Literature

Abstract: Background: We report on a patient with squamous cell anal carcinoma and liver metastases, who underwent multimodal treatment for cure, consisting of repeated partial hepatectomy in combination with chemoradiotherapy. Patients and Methods: A 54-year-old woman presented with squamous cell anal carcinoma and liver metastases. She was treated with a combination of chemoradiotherapy for the primary tumor and then underwent surgery for liver metastases. 2 and 5 years after presentation, the patient underwent repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In most of these reports cisplatin was used as backbone of treatment resulting in response rates of about 50% and median overall survival of 15–33 months depending on patient selection. In single patients, an aggressive multimodality approach including resection of (liver) metastases, irradiation of para-aortic lymph nodes or intra-arterial chemotherapy provided long-term survival [11,12]. The largest prospective clinical trial published thus far was conducted by the Eastern Cooperative Group (ECOG) [10].…”
Section: Introductionmentioning
confidence: 99%
“…In most of these reports cisplatin was used as backbone of treatment resulting in response rates of about 50% and median overall survival of 15–33 months depending on patient selection. In single patients, an aggressive multimodality approach including resection of (liver) metastases, irradiation of para-aortic lymph nodes or intra-arterial chemotherapy provided long-term survival [11,12]. The largest prospective clinical trial published thus far was conducted by the Eastern Cooperative Group (ECOG) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Two and 5 years after presentation, the patient underwent repeated partial hepatectomies for recurrent liver disease. Five months after completing therapy and 71 months after the initial diagnosis, she remained in good health with no evidence of disease (13).…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have shown a good response of the disease to a combination of systemic chemotherapy and regional control of hepatic lesions either through resection [22,23] or through intraarterial chemotherapy [11•]. A case report by Gurfinkel et al noted that a patient proceeded to receive neoadjuvant 5-FU and cisplatin and underwent hepatic resection of segments 3 and 6.…”
Section: Biologic Therapymentioning
confidence: 99%